Phytosociology and periods of weed interference in pineapple cv. Pérola according to spacing - Antônio Barbosa da Silva; Renan Cantalide de Souza; Jorge Luiz Xavier Lins Cunha; Lima, Lucas Alceu Rodrigues; Luiz Eugênio Bulhões; João Virginio da Silva Neto (Comunicata Scientiae, 2023)
The degree of weed interference depends on factors related to the crop, the weed community, the environment, the period of coexistence, and the available resources (water, nutrients, and light). Thus, the period of coexistence between the crop and weeds is a crucial factor in defining the potential for loss of productivity. This research aimed to carry out a phytosociological study and determine the periods of weed interference in the pineapple crop as a function of spacing. The evaluated variables of the weed community were frequency, density, abundance, importance value index, and weed dry mass. Pineapple productivity and °Brix of fruits were determined for the periods of interference. The botanical families Asteraceae and Poaceae presented the highest number of weed species. Digitaria insularis, Richardia grandiflora, Panicum maximum, Cyperus rotundus, and Cenchrus echinatus were the main weeds found. The pre-interference period, total interference prevention period, and critical interference prevention period were 35 days, 35 to 365 days, and 330 days after planting, respectively. The reduction in productivity due to weed interference throughout the cycle can be higher than 80% for the pineapple crop.